THE EFFECT OF USING FLIPPED LEARNING STRATEGY IN IMPROVING STUDENTS’ SPEAKING SKILL IN HYBRID LEARNING - Verina Ainur Izzami Hariyanto; Yuri Lolita (Globish: An English-Indonesian Journal for English, Education, and Culture, 2023)
The purpose of the study was to determine the the effect of the Flipped Classroom method application on students' speaking skill in hybrid learning. The term "flipped classroom" describes a teaching method in which teachers have students complete their assignments during class time while doing the usual lecture at home. The study was conducted at a vocational high school in Surabaya. There were 18 students who were majoring Online Business And Marketing class involved as the participant. Experimental research with the pre-experimental method was used in this research. The research design of the study is a one-group pretest-posttest. The obtained data was analyzed using T-test and presented as quantitative data by the researcher. The findings of this study indicate that the ttest = 8.416 and ttable = 1.740 ( ttest > ttable) while the significance value of 0.000 < 0.05, the H0 is declined whereas the H1 is approved. In conclusion, the Flipped Classroom is effective in enhancing vocational high school students’ speaking skills.